Oral Antihypertensive Regimens (Nifedipine-retard, Labetalol, and Methyldopa) for Management of Severe Hypertension in Pregnancy: An Open-Label, Randomized Controlled Trial. Issue 3 (September 2020) - Easterling, T.; Mundle, S.; Bracken, H.; Parvekar, S.; Mool, S.; Magee, L.A.; von Dadelszen, P.; Shochet, T.; Winikoff, B.
Abstract : ( Lancet . 2019;394:1011–1021) Hypertension complicates ∼10% of pregnancies, and is associated with adverse outcomes for the mother and child. Severe hypertension in pregnancy, defined as a systolic blood pressure ≥160 mm Hg or diastolic blood pressure ≥110mm Hg, is considered an obstetric emergency requiring urgent antihypertensive treatment to prevent cardiovascular or cerebrovascular events. There are currently insufficient data on medications used to treat severe hypertension in pregnancy. This study directly compared 3 oral drugs—labetalol, nifedipine, and methyldopa—for efficacy and safety when used for the treatment of severe hypertension in pregnancy.